2023
DOI: 10.3389/fimmu.2023.1191033
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of peripheral natural killer cells in primary central nervous system lymphoma

Abstract: BackgroundPrimary central nervous system lymphoma (PCNSL) is an aggressive extranodal non-Hodgkin lymphoma with a poor prognosis. We aimed to evaluate the prognostic impact of circulating NK cells in PCNSL.Materials and methodsPatients diagnosed with PCNSL who were treated at our institution between December 2018 and December 2019 were retrospectively screened. Patient variables including age, sex, Karnofsky performance status, diagnostic methods, location of lesions, lactate dehydrogenase, cerebrospinal fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…In the present work, the authors found decreased numbers of peripheral blood NK cells, a finding corroborated by other investigators 22 and even in patients with primary central nervous system NHL in which the low numbers of NK cells were associated with poor outcomes, especially in those having <165 NK cells/μL 23 …”
Section: Discussionsupporting
confidence: 92%
“…In the present work, the authors found decreased numbers of peripheral blood NK cells, a finding corroborated by other investigators 22 and even in patients with primary central nervous system NHL in which the low numbers of NK cells were associated with poor outcomes, especially in those having <165 NK cells/μL 23 …”
Section: Discussionsupporting
confidence: 92%
“…Lin et al conducted a study on 161 patients with PCNSL and found that individuals who responded to treatment had a higher median of circulating NKC and NK cell proportion compared to those who did not respond. Their study revealed that PCNSL patients who have a higher baseline NKC display longer OS than those with a low NKC [ 91 ]. Consequently, NKC in NHL patients represents a prognostic biomarker for the assessment of clinical outcomes.…”
Section: Nk Cell Defects In Nhlmentioning
confidence: 99%